The repercussions of digital bullying on social media users - Al-Turif, Ghada A. R.; Al-Sanad, Hessa A. R. (Frontiers in Psychology, 2023)
Objective: This study aims to examine the repercussions of digital bullying on social media users, especially among university students in Saudi Arabia. Methods: It adopts a descriptive approach based on a social survey method with a sample of 640 male and female students from selected universities. A questionnaire was used to collect the data and to measure the repercussions of digital bullying on the victims, their families, and the society. Results: The findings reveal that most of the respondents agree that digital bullying has negative consequences for all the stakeholders involved. The results also indicate that female students are more aware of the repercussions of digital bullying than male students. Conclusion: The study recommends enhancing public awareness through organizing conferences, seminars, and workshops on the issue of digital bullying, and implementing and enforcing strict laws and penalties to punish the perpetrators and to prevent and reduce the harms of digital bullying.